AKIBAT HUKUM JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN MENURUT UU NOMOR 42 TAHUN 1999 - Muhammad Hilmi Akhsin; Anis Mashdurohatun (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
ABSTRACTFiduciary agreements by notarial deed are not sufficient, but should be continued with fiduciary registrants. Fiduciary agreements set forth in notarial deeds without registration do not grant preferential rights to fiduciary recipients. Whereas the objective of Law Number 42 Year 1999 is basically to provide legal protection for creditors from losses caused by default from debtor. From this, the authors in this thesis take the title